Bilateral Pleomorphic Ductal Carcinoma Of Breast- A Rare Presentation With Its Diagnostic Dilemma - Mandal, Meghadipa; Chowdhury, Anadi Roy (International Journal of Human and Health Sciences (IJHHS), 2022)
Pleomorphic carcinoma of breast is a rare morphological subtype of Invasive Breast Carcinoma No Special Type (IBC NST), which has histomorphological overlap with other entities. Here we present such a case with bilateral breast involvement in 45 years old nulliparous woman with family history of breast carcinoma. Typical numerous multinucleated cells (>50%) with marked pleomorphism and wide areas of necrosis were histopathological presentation. AE1/AE3 and Vimentin were positive. Ki-67 labelling index was high along with HER2 amplification. Important differentials were IBC NST with Osteoclast-like giant cells, Choriocarcinomatous pattern, metaplastic carcinoma & metastatic disease all of which was ruled out with proper clinical, histological & immunohistochemical approach. Despite the aggressive nature of the neoplasm and presence of adverse prognostic factors, this case responded well with adjuvant chemotherapeutic regimen. International Journal of Human and Health Sciences Vol. 06 No. 02 April’22 Page: 213-216